Effect of mat pilates training program on functional fitness in older adults - Poli Borah; Ikram Hussain; Lakshyajit Gogoi; Karuppasamy Govindasamy; Surojit Sarkar; Masilamani Elayaraja; Ethiraj Balaji; Hemantajit Gogoi (IP Iermakov S.S., 2024)
Background and Study Aim. The increasing recognition of pilates as a comprehensive exercise regimen tailored to the needs of the elderly population underscores its growing importance. This shift in emphasis reflects a growing awareness of the potential benefits of pilates for older adults' overall well-being. Study Aim - to investigate the potential benefits of a six-week mat pilates training (MPT) program on the functional fitness of older adults. Material and Methods. In total, a group of 30 elderly individuals (i.e., NMale=18 and NFemale=12), who regularly frequented a local playground, participated in a quasi-experimental study. The study involved pre-test and post-test assessments and was conducted over a period of six weeks. Participants underwent an MPT program (six days a week for six weeks, 60 minutes per session). Were assessed for various functional fitness parameters: lower-body strength (LBS), upper-body strength (UBS), aerobic endurance (AE), lower-body flexibility (LBF), upper-body flexibility (UBF), agility (AG), and Body Mass Index (BMI). A paired-sample t-test was used for statistical analysis. Results. The MPT resulted in significant (p<0.001) improvement in LBS (9.71%), UBS (8.33%), AE (7.11%), LBF (13.48%), UBF (98.78%) and AG (10.52%) post-intervention. However, no significant change was noted in the BMI. Conclusions. A MPT program significantly enhances various dimensions of functional fitness in older adults, excluding BMI. The study results have profound implications for older individuals' well-being and quality of life. Given the global trend towards an ageing population, pilates emerges as an essential intervention for promoting active ageing, potentially improving daily functioning, reducing fall risk, and enhancing independence in the elderly.